Useful clinical features for the selection of ideal patients with strial fibrillation for mapping and catheter ablation - Mehta,Niraj (2002)
OBJECTIVE: To identify useful clinical characteristics for selecting patients eligible for mapping and ablation of atrial fibrillation. METHODS: We studied 9 patients with atrial fibrillation, without structural heart disease, associated with: 1) antiarrhythmic drugs, 2) symptoms of low cardiac output, and 3) intention to treat. Seven patients had paroxysmal atrial fibrillation and 2 had recurrent atrial fibrillation. RESULTS: In the 6 patients who underwent mapping (all had paroxysmal atrial fibrillation), catheter ablation was successfully carried out in superior pulmonary veins in 5 patients (the first 3 in the left superior pulmonary vein and the last 2 in the right superior pulmonary vein). One patient experienced a recurrence of atrial fibrillation after 10 days. We observed that patients who had short episodes of atrial fibrillation on 24-hour Holter monitoring before the procedure were those in whom mapping the focus of tachycardia was possible. Tachycardia was successfully suppressed in 4 of 6 patients. The cause of failure was due to the impossibility of maintaining sinus rhythm long enough for efficient mapping. CONCLUSION: Patients experiencing short episodes of atrial fibrillation during 24-hour Holter monitoring were the most eligible for mapping and ablation, with a final success rate of 66%, versus the global success rate of 44%. Patients with persistent atrial fibrillation were not good candidates for focal ablation.